Mapping of Featured Micro-small-medium Enterprises in Buleleng Regency, Bali, Indonesia - Antara, Made; Sumarniasih, Made Sri (International Journal of Economics and Financial Issues, 2017)
The results of the research were obtained, featured MSME's in Buleleng regency namely: (a) The agricultural sector are rice paddy, cattle, mango, cloves, pork, coffee, wine, fish, cocoa and strawberry; (b) The manufacturing sector are rice milling unit (RMU), processing and preserving fish, processing of red sugar, ingkewebbing industrial, weaving handicraft industrial, poultry slaughterhouses, refill drinking water, food products of various chips, processing of coffee powder, and industrial of dodol from fruits; (c) The construction sector are a building construction contractor; (d) Trade, hotels and restaurants is are jasmine hotel, restaurant/ café, HP counter, homestay, villa, minimarket and retail shops (klontong), trading of agricultural products, and Artshop; (e) transport and communications sector are the land transport of goods (trucks), urban and rural passenger transport, package delivery services, motorcycle transport (ojek), rent car, and netcafe; (f) the financial sector, leasing, and other services are village credit institutions (LPD), saving and loan cooperation (KSP), village unit cooperation (KUD), people credit banks (BPR), and money changer; (g) The other services sector are barber shop and beauty salon, sewing of clothes, services of workshop cars and motorcycles, photocopying, tour guides, laundry, early childhood education (PAUD), a tourist attraction of Gitgit waterfall, tourist attractions of Lovina beach, and tourism attraction of Air Sanih. Keywords: Micro-Small-Medium Enterprises (MSMEs), Featured, Mapping. JEL Classifications: L32, Q13